Lipedema: From Women’s Hormonal Changes to Nutritional Intervention - Inês Tomada (Endocrines, 2025)
Lipedema is a chronic disease of the subcutaneous adipose tissue that mostly affects women. The etiopathogenesis of the disease is still poorly understood. Lipedema typically develops after major hormonal changes, such as puberty, pregnancy, and menopause. Alongside genetic susceptibility, the pathophysiological mechanism involving hormonal changes is mostly linked to aberrantly expressed estrogen receptors in adipose tissue. Lipedema has no known cure, and current therapies aim primarily to reduce symptoms, avoid complications, and slow the disease progression. Achieving or maintaining a healthy body composition, preserving or regaining mobility and functionality, preventing the progression of disease, and reducing pain and other symptoms are all possible outcomes of proper nutrition and weight management. Since nutrition may provide a long-term solution to control almost constant inflammation, it should be a major part of lipedema treatment. Despite the lack of a specific, scientifically supported diet for lipedema patients, several dietary approaches have been suggested. In this comprehensive narrative review, supported by published revisions and peer-reviewed studies following scrutiny of digital medical databases, the current state of knowledge and theories regarding the hormonal etiopathogenesis of lipedema are presented, as well as the role of nutritional intervention in reducing its symptoms and progression.